Taking a multiple-use approach to meeting the water needs of poor communities brings multiple benefits - International Water Management Institute; International Water and Sanitation Centre; Global Water Partnership (International Water Management Institute, 2006)
This briefing was produced by International Water Management Institute (IWMI), the IRC International Water and Sanitation Centre, the Technical Committee of the Global Water Partnership (GWP) and the GWP Advisory Center at IWMI. It draws primarily on research from the Multiple Use Systems (MUS) project and the Productive Uses of Water Thematic Group (Prodwat) (see references for further reading). The brief complements Catalyzing Change, the GWP handbook for developing IWRM and water efficiency strategies and plans, and the associated policy and technical briefs. Single-use approaches to water development and management do not reflect the realities of poor people?s water use. People use domestic water supplies for activities such as irrigating backyard gardens, keeping livestock, fishing, processing crops and running small-scale enterprises. In areas without adequate domestic water supply, they use irrigation water to meet household needs, such as drinking and bathing, as well as to support a range of incomegenerating activities in addition to crop production. A more integrated, multiple-use approach can maximize the health benefits and productive potential of available water supplies?leading to increased incomes, improved health and reduced workloads for women and children. Systems that cater to multiple uses are also more likely to be sustainable, because users benefit more from them, have a greater stake in them, and are more willing and better able to pay for them. policy-makers, planners, and project designers need to enable and support a multiple-use approach by developing the necessary policies, capacities, and institutions. Incorporating provision for multiple uses into plans for meeting the Millennium Development Goals, Poverty Reduction Strategy Papers, and IWRM and water efficiency plans and strategies is a start.